Evaluación de la influencia de los hábitos orales, sobre el biotipo facial en la población de 6 a 18 años del municipio de Buenavista, Quindío. (2023)
Introduction: Facial biotype corresponds to a set of morpho-differential characteristics of people, in relation to certain features in common of the facial skeleton, determined by genetics and environment. The prevalence of dentofacial anomalies, also called malocclusions, may be related to oral habits. Objective: To determine the prevalence of oral habits and changes in the facial biotype present in the population aged 6 to 18 years in the municipality of Buenavista, Quindío. Material and methods: A descriptive study was carried out that included 219 infants and adolescents aged 6 to 18 years in the municipality of Buenavista, Quindío; parameters for the analysis of oral habits were included, as well as the determination of facial biotype by means of the opening angle, Glatzel tests, Payne's technique). Descriptive analysis (frequencies and percentages) and Chi-square test were performed to evaluate if the number of habits was related to facial biotype.